Pengaruh Peran Perawat sebagai Edukator terhadap Kepatuhan Minum Obat pada Pasien Hipertensi di Poliklinik Rumah Sakit Primaya - Asmaul Husnah; Nur Qamariyah; Nursyamsiyah Nursyamsiyah (Pusat Riset dan Inovasi Nasional, 2025)
Hypertension is a non-communicable disease that can nonetheless lead to death. One of the essential factors in achieving therapeutic effectiveness and improving patients' quality of life is medication adherence. Conversely, non-adherence to prescribed medication is one of the main causes of treatment failure. Nurses play a critical role as educators by helping patients gain knowledge about medical care and treatment procedures, thereby providing the necessary information to improve adherence to hypertension medications. The objective of this study was to analyze the effect of the nurse's role as an educator on treatment adherence among hypertensive patients. This research employed a cross-sectional approach involving 60 hypertensive respondents at the outpatient clinic of Primaya Hospital. Data were collected using validated questionnaires assessing both the nurse's role and patient medication adherence, and analyzed using the Mann-Whitney test. The results showed that the nurse's role as an educator was rated as “good” by 34 respondents (56.7%), and that medication adherence among hypertensive patients at Dinoyo Health Center was “high” in 43 respondents (71.7%). The statistical analysis revealed a significant relationship between the nurse's educational role and medication adherence, with a p-value of 0.000. It can be concluded that there is a significant effect of the nurse's role as an educator on treatment adherence. The better the nurse performs their role as an educator, the higher the patient's adherence to antihypertensive medication.